Improving Msme Performance: Management Accounting Strategies, Leadership Quality and Market Orientation - Merna Surjadi; Tandry Whittleliang Hakki; Frans Saputra (DINASTI RESEARCH, 2023)
The micro, small and medium enterprises (MSMEs) sector plays an important role in the national economy, but high competition makes it difficult for businesses to develop. Company performance is used as a benchmark for assessing business operating systems so it is necessary to know the factors that affect business performance, one of which is the strategic management accounting method. In the context of financing to the MSME sector–as a 61.07 percent contributor to GDP, so that economic growth is maintained, the government has also given a signal to continue to increase financing to MSMEs. The purpose of this research is to test and analyze whether Mannaement Accounting Strategy, Leadership Quality and Market Orientation affect the Performance of Micro, Small and Medium Enterprises (MSMEs). This study uses primary data which is conducted by distributing questionnaires to MSME owners in DKI Jakarta and its surroundings. The method used in this study is quantitative, because this method can test the relationship between variables in a model, both the relationship between variables and their constructs and the relationship between constructs. The results of this study indicate that management accounting strategies have an effect on MSME performance; leadership quality does not affect MSME performance; Market orientation has no effect on MSME performance.